The Effect of Different Molar Access Cavity Designs on Root Canal Shaping Times Using Rotation and Reciprocation Instruments in Mandibular First Molars - Vorster, Martin; van der Vyver, Peet J.; Markou, George (My University, 2022)
Introduction: The aim was to compare the glide path and final preparation times of WaveOne Gold and TruNatomy in conjunction with two different endodontic access cavity designs in extracted human molar teeth. Methods: 60 extracted human mandibular molars with mesiobuccal canals were selected and randomly divided into two different access cavity design preparation groups (n = 30). Traditional access cavities (TAC) and conservative access cavities (CAC). Within each cavity design group, the 30 teeth were divided in to two instrumentation groups (WaveOne Gold Primary (n = 15) and TruNatomy Prime (n = 15)). Group 1: TAC, #10 stainless steel manual K-file followed by WaveOne Gold Glider and WaveOne Gold Primary. Group 2: CAC, #10 stainless steel manual K-file followed by WaveOne Gold Glider and WaveOne Gold Primary. Group 3: TAC, #10 stainless steel manual K-file followed by TruNatomy Orifice Modifier and Glider and TruNatomy Prime. Group 4: CAC, #10 stainless steel manual K-file followed by TruNatomy Glider and TruNatomy Prime. Glide path and final preparation times were recorded. Results: Shaping time with TruNatomy Glider in combination with TruNatomy Prime instruments were faster compared to the WaveOne Gold Glider/ WaveOne Gold Primary instruments regardless of the type of access cavity preparation. TAC design yielded faster preparation time (38.2 ± 4.57 seconds) compared to the CAC (55.6 ± 6.91 seconds) in the WaveOne Gold Glider/ WaveOne Gold Primary instrumentation group. No difference was found between the different access cavity design groups in combination with TruNatomy Glider/TruNatomy Prime preparation. Conclusion: Preparation time with TruNatomy Glider and Prime instruments was significantly faster than WaveOne Gold Glider/WaveOne Gold Primary, regardless of the access cavity design. TAC design in combination with WaveOne Gold Glider/ WaveOne Gold Primary instrumentation resulted in faster preparation time compared to WaveOne Gold Glider/WaveOne Gold in combination with the CAC design.
Keywords: Canal preparation time; TruNatomy; WaveOne Gold; conservative access cavity; traditional access cavity